Assessment of tempranillo grapes quality in the vineyard by Vitur score-sheet - Javier Tardáguila; Fernando Martínez de Toda (OENO One, 2008)
Aims: The main objective of this study is to determine whether the Vitur score-sheet could be applied as a reliable method for assessing winegrape quality in the vineyard. Methods and results: Grape assessment of vineyards (Vitis vinifera L. 'Tempranillo') in the Rioja Appellation was performed by Vitur scoresheet, proposed by Tardáguila and Martínez de Toda (2005). Vegetative growth, yield components and the chemical composition of the grapes were also determined. Correlation analysis between vineyard variables and the chemical composition of the grapes were performed to identify characteristics associated with grape quality. The Vitur value was the studied parameter that displayed the best correlation with the chemical composition of the grapes. Vitur value was significantly correlated with extractable and total anthocyanins, total polyphenols index, sugar content, titratable acidity, tartaric acid and malic acid content. Conclusions: This article reports a new approach to winegrape assessment in the vineyard. The Vitur methodology was a fast and reliable method for assessing Tempranillo grape quality in the vineyard under Spanish conditions. Significance and impact of study: The results suggest that wine industry could use a Vitur methodology, as tool to classify grapes in a simple and rational manner before the harvest and winemaking